2021
DOI: 10.3390/vaccines9060655
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Responses during Human γ-Herpesvirus Infections

Abstract: Herpesviruses are main sculptors of natural killer (NK) cell repertoires. While the β-herpesvirus human cytomegalovirus (CMV) drives the accumulation of adaptive NKG2C-positive NK cells, the human γ-herpesvirus Epstein–Barr virus (EBV) expands early differentiated NKG2A-positive NK cells. While adaptive NK cells support adaptive immunity by antibody-dependent cellular cytotoxicity, NKG2A-positive NK cells seem to preferentially target lytic EBV replicating B cells. The importance of this restriction of EBV rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 125 publications
(163 reference statements)
0
7
0
Order By: Relevance
“…As further evidence of the disarray in NK results in CFS/ME, Rivas et al in 2018 [7] reported a lower expression of NKG2C, an activating receptor that recognizes Human Leucocyte Antigen E (HLA-E), in contrast to an earlier study where no differences were observed and with the differences attributed to frozen PMBC used in one study and whole blood in the other [47]. Importantly, altered expression of activating and inhibitory NK cell receptors are evident in chronic cytomegalovirus (CMV) infections and in coinfections with other viruses, notably Epstein-Barr virus (EBV) [48]. In patients with severe ME/CFS, defects in protein kinase gene expression in NK cells has been reported [49].…”
Section: Natural Killer Cell Analyses In Me/cfsmentioning
confidence: 83%
“…As further evidence of the disarray in NK results in CFS/ME, Rivas et al in 2018 [7] reported a lower expression of NKG2C, an activating receptor that recognizes Human Leucocyte Antigen E (HLA-E), in contrast to an earlier study where no differences were observed and with the differences attributed to frozen PMBC used in one study and whole blood in the other [47]. Importantly, altered expression of activating and inhibitory NK cell receptors are evident in chronic cytomegalovirus (CMV) infections and in coinfections with other viruses, notably Epstein-Barr virus (EBV) [48]. In patients with severe ME/CFS, defects in protein kinase gene expression in NK cells has been reported [49].…”
Section: Natural Killer Cell Analyses In Me/cfsmentioning
confidence: 83%
“…Similar to EBV, KSV infects primarily cells of the B lymphocyte lineage, where it can establish latency. It also shares with EBV an oncogenic potential, leading, in particular, to primary effusion lymphoma [165][166][167]. A role for γδ T cells in HHV-8 infections has been reported in one study [168], where patients selected for shedding HHV-8 in saliva (n = 7) were compared to seronegative controls.…”
Section: γδ and Ksv/hhv-8mentioning
confidence: 98%
“…CMV infection results in a dramatic change of the expression of NKG2A/C HLA-E-binding receptors on NK cells. NKG2A is an inhibitory receptor expressed on early differentiated NK cells, whereas NKG2C is activatory and expressed on terminally differentiated memory-like NK cells [167]. During CMV infection NKG2C + NK cells expand while NKG2A + NK cells are lost in transplant patients, but also in healthy CMV + children [218][219][220].…”
Section: Hiv-hhv Co-infectionsmentioning
confidence: 99%
“…NK cells probably play a role during gammaherpesvirus infection (Münz, 2021). Accordingly, to counteract this arm of the immune response, human gammaherpesviruses have developed various strategies to evade NK cell-mediated immune responses, mostly by suppressing the signaling of activating receptors and triggering the signaling of inhibitory receptors (Münz, 2021). Multiple observations support the theory that NK cells contribute to the cellular immune response following human gammaherpesvirus infections.…”
Section: The Nk Cell-mediated Response During Ebv and Mhv68 Infectionmentioning
confidence: 99%